A study on biomarkers in workers exposure to benzene - Cao, J.; Jian, Le (Chinese Preventive Medicine Association & HuaNan Centre for Occupational Disease Prevention and Treatment, 2002)
A cross-sectional study was conducted in China at a shoe manufacturer in Zhejiang Province to develop biomarkers for workers exposed to benzene. Results showed that workers' urinary concentrations of phenol and S-phenylmercapturic acid (PMA) reached to the peak levels at the end of shift works and concentrations of blood benzene had the similar trend. Results suggest that blood benzene can reflect the recent body burden of benzene exposure and urinary PMA and phone can reflect the absorbent and metabolic situation of benzene in human body. Thus it is practicable and convenient to use urinary metabolisms of benzene as the biomarkers in regular biomonitoring programs.